2022
DOI: 10.1007/s00520-022-07456-x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue trajectories during pediatric ALL therapy are associated with fatigue after treatment: a national longitudinal cohort study

Abstract: Objective Fatigue is one of the most prevalent and distressing symptoms reported by survivors of childhood cancer. There is currently a lack of longitudinal studies on cancer-related fatigue, and especially on the relationship between the course of fatigue during treatment and fatigue at follow-up. The purpose of the current study was therefore to investigate if the course of fatigue during treatment, treatment intensity, serious adverse events, sex, or age at diagnosis are associated with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…It is possible that sex differences previously detected by Cheung et al (2017) are more salient in adolescence, in which females can be particularly vulnerable (Pfeifer & Allen, 2021). Still, our results are consistent with several other studies in the childhood cancer literature, that have reported similar levels of fatigue among males and females (Frederick et al, 2016;Irestorm et al, 2023;Zeller et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is possible that sex differences previously detected by Cheung et al (2017) are more salient in adolescence, in which females can be particularly vulnerable (Pfeifer & Allen, 2021). Still, our results are consistent with several other studies in the childhood cancer literature, that have reported similar levels of fatigue among males and females (Frederick et al, 2016;Irestorm et al, 2023;Zeller et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…A prevalent (Hamre et al, 2013;van Deuren et al, 2022), distressing (Hamre et al, 2013;Kanellopoulos et al, 2013), and relatively persistent (Irestorm et al, 2023;Zeller et al, 2014) symptom in survivors of childhood ALL is fatigue. Fatigue may be described as "a sense of tiredness and lack of energy, distinct from sadness and weakness" (Krupp et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This study did not identify any clear risk factors for ongoing fatigue in this patient population at 27-months post treatment. While these findings are in keeping with some earlier evidence indicating no age, sex, or treatment related risk factors to be present 12-months post treatment [31], alternate studies have identified age at diagnosis and female sex to be relevant to fatigue in the childhood cancer survivorship population [13,32,33]. As the current study examined the period directly following treatment completion, as opposed to patients further post-treatment, it seems possible that demographic risk factors go on to emerge further into survivorship.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated that fatigue reported during treatment for acute lymphoblastic leukemia can predict the level of fatigue experienced after end of treatment. 39 It is possible that this also applies to patients after treatment for a brain tumor, and future studies should therefore investigate fatigue during treatment for this group as well.…”
Section: Discussionmentioning
confidence: 99%